Rare bird documentation form for Lesser Black-backed Gull at Mississippi River between Bettendorf, IA and Moline, IL, 1992 - Petersen, Peter C.et al (1992)
Rare bird documentation form for a Lesser Black-backed Gull at Mississippi River between Bettendorf in Scott County, IA and Moline in Rock Island County, IL on January 11, 1992. Epson - sheet feed